STUDY ON THE AGRICULTURAL PRODUCTION EVOLUTION IN CĂLĂRAȘI COUNTY, ROMANIA - Oana Roberta CREȚU; Valentina Constanța TUDOR; Cecilia NEAGU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania is one of the European countries with the most favorable soil and climate conditions in order to obtain quality agricultural productions and in significant quantities, which can cover an important segment of the domestic demand for agri-food products. Despite the considerable potential, the profitability in Romanian agriculture is still modest, indicating a use of production factors below the level of optimal values. Based on these considerations and predicting that in 2021, the population need for agri-food products consumption will increase, as a result of the repatriation of approximately two million Romanian citizens, who worked in the European Union countries due to the crisis generated by Covid-19, we initiated the present study on the agricultural production evolution in Călărași county, in comparison to South Muntenia Region, of which it is part and with the production at national level. For the data processing and interpretation, the method of statistical indicators was used, respectively, the comparative analysis of the researched phenomena. The comparison method was used in the analysis of the data series that covered time periods between 2000 and 2007 and 2008 and 2018, depending on the available data. For each period, the indicators were calculated: average, standard deviation, coefficient of variation and annual growth rate. It results clearly that for the next period it is important to intensify some measures to provide subsidies, to use on large scale the need for irrigation, fertilization and other activities that will give perspective to evolution in this area and lead to the agrio-food security and independence of Romania.